2021
DOI: 10.1016/j.psj.2021.101363
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel chicken astrovirus in China

Abstract: Chicken astrovirus ( CAstV ) is associated with kidney disease and visceral gout, runting and stunting syndrome, and white chick hatchery disease, causing economic losses to the poultry industry worldwide. In this study, 55.6% of 36 clinical samples from Guangdong province in China were positive for CAstV, but negative for other common enteric viruses, including avian nephritis virus, infectious bronchitis virus, fowl adenovirus Group I, Newcastle disease virus, chicken parvovirus, reovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The disease mainly occurs in the goose within 3 weeks mortality rate of 10 to 50% ( Wan et al, 2018 ; Zhang et al, 2018 ). Through pathogen isolation and animal regression experiments, the pathogen causing the disease was determined to be goose astrovirus type 2 ( GoAstV-2 ) ( Wang et al., 2020 , Yang et al., 2018 ; Yin et al, 2021 ). Recently, Clinical reports indicated that goose astrovirus type 1 ( GoAstV-1 ) could cause kidney swelling and visceral gout in goslings, symptomatically indistinguishable from those caused by GoAstV-2 ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The disease mainly occurs in the goose within 3 weeks mortality rate of 10 to 50% ( Wan et al, 2018 ; Zhang et al, 2018 ). Through pathogen isolation and animal regression experiments, the pathogen causing the disease was determined to be goose astrovirus type 2 ( GoAstV-2 ) ( Wang et al., 2020 , Yang et al., 2018 ; Yin et al, 2021 ). Recently, Clinical reports indicated that goose astrovirus type 1 ( GoAstV-1 ) could cause kidney swelling and visceral gout in goslings, symptomatically indistinguishable from those caused by GoAstV-2 ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study, the susceptibility of the cell line to multiplicate Avian Nephritis Virus (ANV) and duck astroviruses (DAstV) was demonstrated as well. Isolation of DAstV-1 was described later on, again with CPE at the 5th passage [147,148]. The same number of passages was reported to induce visible changes in LMH cells during isolation of goose astrovirus [149].…”
Section: Virologymentioning
confidence: 99%
“…Although other viruses have been implicated in cases of RSS, underperformance, and growth checks, recent studies have identified CAstV as the sole etiologic pathogen responsible for the condition in chickens and turkeys (10,12,20,39). Similarly, DNA and RNA extracted from birds exhibiting underperformance, growth checks, and amplified using various enteric virus-specific primers were consistently positive for CAstV but negative for other enteric viruses (9,17,40). Next-generation sequencing and metagenomic approach, as an alternative, have been used to detect the presence of CAstV in the clinical samples (6,41,42).…”
Section: Chicken Astrovirus (Castv) Associated Diseasesmentioning
confidence: 99%
“…In the UK and Malaysia, a seroprevalence investigation reveals seropositivity of CAstV in four generations of broilers and broiler breeder flocks, respectively, (8,9). Since the initial detection of CAstV in the flocks of commercial broiler chickens in 2004 (10), new strains of CAstV have been identified and characterized in chickens worldwide (5,9,(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation